Interactions Between Fibroblast Cells and Laser Beam Welded AISI 2205 Duplex Stainless Steel - Kose, Ceyhun; Kacar, Ramazan; Zorba, Asli Pinar; Bagirova, Melahat; Abamor, Emrah Sefik; Allahverdiyev, Adil M. (KAUNAS UNIV TECH, 2018)
Because of their high mechanical strength, excellent corrosion resistance and good weldability, duplex stainless steels are mostly used in industries such as oil, chemistry, petrochemistry, food and occasionally used in medical industry. These properties have enabled us to use duplex stainless steels in biomedical applications recently. Accordingly, duplex stainless steel material can be highly important to examine the toxic effect on the cells. In this study, the effect of the AISI 2205 duplex stainless steels which are joined by CO2 laser beam welding on viability of L929 fibroblast cells has been studied in vitro for the first time. For this aim, the cells were kept in DMEM/F-12 (Thermofisher Scientific 31331-028) medium for 7 days. The viability study was experimentally studied using the MTT (Thiazolyl Blue Tetrazolium Bromide) method for 7 days. The cell viability of the laser beam welded sample has been detected to be higher than that of the base metal and the control based on 7th day data. According to the obtained results, it was revealed that laser beam welded and base metal AISI 2205 duplex stainless steel has been found suitable to study for biomedical applications.
Keywords: laser beam welding; duplex stainless steel; L929 fibroblast cell; viability; microstructure; IN-VITRO; MECHANICAL-PROPERTIES; CORROSION-RESISTANCE; ORTHODONTIC BANDS; CYTOTOXICITY; WELDABILITY; BEHAVIOR; CRACKING; FLUIDS; Materials Science